Nature positive farm dams - K.U.D.N. Hansani; Lukas Schuster; Peter I. Macreadie; Martino E. Malerba (Agricultural Water Management)
Farm dams are a ubiquitous feature in agricultural landscapes worldwide, functioning as a major source of water for livestock or crop irrigation. Their number is increasing rapidly, often dominating the cumulative surface area of inland waters. Unmanaged farm dams are sources of pollution and pests, whereas sustainably managed farm dams serve as multifunctional assets, supporting biodiversity, improving water quality, and more. Currently, there is a lack of studies that comprehensively assess the impacts of unmanaged farm dams and the benefits of well-managed dams across various domains, including farm productivity and environmental sustainability. To fill this gap, we reviewed the scientific literature to analyse the current knowledge on farm dam management. Farm dam studies (N = 310) constituted 0.1 % of the literature compared to studies on lakes and reservoirs. Nations with high agricultural production are leading farm dam research, especially the USA (26.5 %) and Australia (21.6 %). Hydrology and ecology (63 %) dominate the literature, whereas environment regulation, agriculture, economy, engineering, and social aspects are less represented. Nature positive management can increase the productivity of these assets while minimising their negative impacts. Some examples include limiting livestock access through fencing, enhancing vegetation cover through revegetation, introducing floating wetlands, low-flow bypass devices, and generating renewable energy using floating solar panels and micro-hydro pumps. Integrating carbon or biodiversity crediting for direct and indirect ecosystem services associated with nature positive farm dams is a promising solution for reducing the costs of sustainable farm dam management.